Clinical characteristics and long-term outcomes of warm-type autoimmune hemolytic anemia - Ekarat Rattarittamrong (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Objectives: To study the clinical manifestations, outcomes, and survival of warm-type autoimmune hemolytic anemia (AIHA) patients. Methods: This study was a retrospective single-center study from 2002 to 2013. Clinical data of AIHA patients were reviewed and analyzed. Results: One hundred and one patients were included, of whom 77% were female with a median age of 43 years. Primary AIHA was found in 61% of the patients. The secondary causes were systemic lupus erythematosus (SLE) (64%), solid malignancies (13%), lymphomas (10%), drugs (8%), and infections (5%). Most patients (96%) responded to steroids, which were not different between primary and secondary AIHA. Second-line treatments were required in 33 patients (33%). The indications were steroid dependence (58%), relapse (30%), and others (12%). The most common second-line treatment was cyclophosphamide (52%). The response rate for second-line treatments was 93%. Relapse occurred in 50 patients (50%) in which 58% occurred more than 3 years after diagnosis. The SLE patients relapsed and received second-line therapy more than the non-SLE group (P < 0.001). At the median 53-month follow-up, the overall survival (OS) was 84%. The independent risk factors for OS were age more than 50 years and malignancy. Sepsis was the most common cause of death. Discussion and conclusion: AIHA has a good prognosis and long-term survival especially in young patients without malignancy. Most patients have responded initially to steroids and have a high response rate to second-line therapy. Carefully adjusted and rapid taper of immunosuppressant is necessary to avoid sepsis complications.